The Advantages of the Jigsaw Model in Protista Learning: A Comparative Study of Conventional Learning - Siti Farihah; Novita Vandrianur; Fitri Gumulya (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to determine the differences in the improvement of student learning outcomes on the Protista concept between students taught using the Jigsaw type cooperative learning model and students taught using conventional learning at the Madrasah Aliyah level. Methodology: This study used a quasi-experimental method with a Pre-Test–Post-Test Control Group Design. The sample was determined through purposive sampling and simple random sampling. The research instruments consisted of a 30-item multiple-choice test, an affective observation sheet, N-gain analysis, the Liliefors test, the Fisher exact test, and the t-test. Data processing was carried out using descriptive and inferential statistical analysis. Main Findings: Jigsaw cooperative learning showed higher learning outcomes compared to conventional learning. The average N-gain for the experimental class was 0.33, while the control class was 0.18. The t-test results showed a significant difference (t count 3.75 > t table 1.99). The Jigsaw model also increased student participation, cooperation, responsibility, and engagement in understanding the concept of Protista. Novelty/Originality of this study: The novelty of this research lies in its comparative analysis of the effectiveness of the Jigsaw cooperative learning model on Protista material, which has rarely been specifically studied. This research provides new empirical evidence regarding the influence of Jigsaw on improving students' cognitive and affective learning outcomes, while also expanding the reference list for student-centered biology learning strategies.